Peran Penyuluh Pertanian Pada Kelompok Tani Cabai di Desa Sukanalu Kabupaten Karo: Peran Penyuluh Pertanian Pada Kelompok Tani Cabai di Desa Sukanalu Kabupaten Karo - SIPAHUTAR, BAHAGIA (Jurnal Agriust, 2026)
This study aims to determine the implementation of agricultural extension in Sukanalu Village and the role of Field Agricultural Extension Workers in increasing the productivity of red chili plants in Sukanalu Village, Barusjahe District, Karo Regency. The results of the study show that agricultural extension in Sukanalu Village is carried out by agricultural extension workers visiting farmers at their homes to convey information on how to fertilize red chili plants, the types of fertilizers used, pest and disease control techniques and eradication, and the types of pesticides used. The role of field agricultural extension workers is as motivators and extension workers with a high category, as facilitators and educators with a medium category. The role of agricultural extension workers was able to increase red chili productivity by 14.44%.